Comparative studies on conventional monopole and microwave towers - Balagopal, R.; Rao, N. Prasad; Rokade, R. P; Mohan, S. J. (Journal of Structural Engineering, 2024)
Tubular Steel Pole structures and free standing lattice towers made of angle sections are generally used in tele-communication industry. In urban areas with high density of population, great difficulties are experienced in finding land for installation of conventional lattice towers. Since the pole structures have smaller dimension and occupying lesser space for installation, they found to be a suitable alternate for lattice towers. The comparative study to analyse the structural behavior of both these structures seldom exist in literature. Hence in the present study, self-supporting Mirowave (Mw) lattice tower and telescopic steel tubular pole of 30m and 40m height is considered. The behavior of these structures is studied under same wind speed, terrain category and antennae loading. The wind load on these structures are calculated based on IS 875 (Part 3): 1987. The lattice tower made of steel angle sections is modeled by using beam elements and four noded plate element is used for modeling the shaft of the pole using NE NASTRAN software. The deflection pattern for various stages of loading was recorded during static analysis for both the structures. Weight comparison is also made. Simplified numerical model of the lattice tower and pole structure is developed based on model order reduction technique in MATLAB platform to compute the modal characteristics of these structures and subsequently compared with results of FE analysis. Based on the above results, conclusions are drawn.